Informação étnico-racial no âmbito dos programas de pós-graduação em psicologia - Santana, Sérgio Rodrigues de (2016)
The information available to be accessed, used, and properly assimilated by the subject, enable cognitive growth and individual as well as the economic and social growth too. In this context of dissemination of information to produce of the knowledge must be articulated to the multicultural context through of the promotion of diversity and ethnic and racial equality. Regarding to ethnic and racial information, focusing the black population, it reveals as any process, knowledge or registered thing, registered or accommodated in a physical or digital support, passive of the significance linguistic (psychological) of the subjects which uses it. This kind of information has the potential to produce knowledge about the historical and cultural elements of a particular ethnic and racial group. This study investigates the production of ethnic and racial information in the context of postgraduate in Psychology among years 2010 and 2015. The specifics objectives this search are outlined: a) Identify the programs of postgraduate in psychology in Brazil; b) Identify the digital environments used to store and disseminate theses and dissertations of Brazilian programs of postgraduate in Psychology; c) Mapping ethnic and racial themes about black population in dissertations and theses of Brazilian programs of postgraduate in Psychology in the period 2010-2015. Research is understood from the phenomenological method that demonstrate to investigate the essence of the phenomena. Is positioned in the quantitative and qualitative mixed approach and to process the data was used the Alceste software. This study is relevant, therefore, it contributes to the continuation of investigations into the black population in Brazil that has intensified in the last five years. Its importance to field of the Information Science to figure from the social responsibility of IC as a knowledge system. The results show that the scientific production of theses and dissertations in the programs of postgraduate in Psychology in Brazil, producing ethnic and racial information whose essence is of black people subjects in the educational context, in the context of racial quota policies, and culture elements , identity and African and afrodescent memory.